A Study on Freedom of Speech Based on Politness Strategies Used by the Jakarta Post Readers - Muhartoyo, Muhartoyo (Bina Nusantara University, 2011)
Freedom of speech or expression is an indication of a democratic country. Indonesia that has transformed itself from an authoritarian government during the New Order Era into a democratic country in the so called Reform Era. This study is an attempt to find out the existence of freedom of expression in the Indonesian printed media. The data were collected from the Jakarta Post Readers’Forum from 1 November 2010 to 28 February 2011. The data were then classified and analysed based on Brown and Levinson’s theory of politeness strategies. The data analysis shows that a lot of utterances can be classified under Politeness Strategy 1 (the least polite strategy out of the four strategies). This proves that people are now free to express their ideas and criticisms in the most direct manner without fear of being arrested or reprimanded by the government. Even the sensitive issues like SARA (Ethnic, Religion, Racial and Communal) conflicts can be freely discussed in the printed media. Thus freedom of expression is prevailing in Indonesia under the New Era government.